2021
DOI: 10.1039/d0ra07991j
|View full text |Cite
|
Sign up to set email alerts
|

The yield and quality of Pleurotus abieticola grown on nematode-infected Pinus massoniana chips

Abstract: In this study, we investigated the use of nematode-infected Pinus massoniana chips (NPC) as the main ingredient in Pleurotus abieticola substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…22 P. eryngii showed an anti-atherosclerotic effect in ApoE-deficient mice. 23 P. abieticola is distributed in northeastern and northwestern China and Russia and has been successfully cultivated; 24 few studies have reported its biological activity. Earlier, we extracted a water-soluble polysaccharide from the fruiting bodies of P. abieticola , known as PAPS1, which exhibits immune-enhancing activity by promoting cellular immune response.…”
Section: Introductionmentioning
confidence: 99%
“…22 P. eryngii showed an anti-atherosclerotic effect in ApoE-deficient mice. 23 P. abieticola is distributed in northeastern and northwestern China and Russia and has been successfully cultivated; 24 few studies have reported its biological activity. Earlier, we extracted a water-soluble polysaccharide from the fruiting bodies of P. abieticola , known as PAPS1, which exhibits immune-enhancing activity by promoting cellular immune response.…”
Section: Introductionmentioning
confidence: 99%
“…euosmus , Pleurotus eryngii , Pleurotus ostreatus , P . populinus , and Pleurotus pulmonarius , the treatment process incurs high costs ( Guo et al, 2021 ). If Pleurotus species can directly use coniferous substrate without treatment, it could help reduce production costs and increase income.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have focused on Pleurotus abieticola (P. abieticola) , originally found in northeastern and northwestern China and in the Russian Far East [ 17 , 18 ]. Currently, P. abieticola is successfully cultivated on nematode-infected Pinus massoniana chips [ 19 ]. The few reports referring to its bioactive components and medicinal properties strongly limit its application both as a food and as a medicine.…”
Section: Introductionmentioning
confidence: 99%